Pd catalysts supported on dual-pore monolithic silica beads for chemoselective hydrogenation under batch and flow reaction conditions. Issue 18 (19th August 2020) - Yamada, Tsuyoshi; Ogawa, Aya; Masuda, Hayato; Teranishi, Wataru; Fujii, Akiko; Park, Kwihwan; Ashikari, Yosuke; Tomiyasu, Noriyuki; Ichikawa, Tomohiro; Miyamoto, Riichi; Bai, Hongzhi; Matsuyama, Kiyoshi; et al.
Abstract : Two different types of palladium catalysts supported on dual-pore monolithic silica beads [5% Pd/SM and 0.25% Pd/SM(sc)] for chemoselective hydrogenation were developed. Abstract : Two different types of palladium catalysts supported on dual-pore monolithic silica beads [5% Pd/SM and 0.25% Pd/SM(sc)] for chemoselective hydrogenation were developed. Alkyne, alkene, azide, and nitro functionalities and the aromatic N -Cbz protecting group were chemoselectively hydrogenated using 5% Pd/SM. On the other hand, 0.25% Pd/SM(sc) showed unique and higher hydrogenation catalyst activity toward a wide variety of reducible functionalities. Furthermore, the catalyst activities of both 5% Pd/SM and 0.25% Pd/SM(sc) under flow hydrogenation conditions were also evaluated. A pre-packed 5% Pd/SM cartridge could be used continuously for at least 72 h without any loss of catalyst activity. The 0.2% Pd/SM(sc) catalyst prepacked in a cartridge showed high catalyst activity for the flow hydrogenation of trisubstituted alkenes under mild reaction conditions.